Chert availability and prehistoric exploitation in the Near East - Delage, Christophe (BAR, 2007)
Chert availability and prehistoric exploitation in the Near East : an introduction / Christophe Delage -- Distribution and petrographic characteristics of cherts in Syria / Darrell F.G. Long and Patrick J. Julig -- Chert identification and characteristics in Northern Israel / Christophe Delage -- Purple-pink flint sources in Jordan / Gary O. Rollefson, Leslie Quintero, and Philip Wilke -- Distribution of flint in Turkey, from 10,000 to 6,000 cal BC. Case study - Çatalhöyük / Ana Bezić -- Patterns of flint exploitation and use at Neolithic settlements of Syria / Yoshihiro Nishiaki -- Fluviatile terraces as "flint mines" in the Levant / Lorraine Copeland -- Use of raw material at Yabrud Rockshelter I / Rose L. Solecki and Ralph S. Solecki -- Sourcing of archaeological flints from the middle to upper Palaeolithic transition, Jerf al-Ajla Cave, Syria / Patrick J. Julig ... [et al.] -- The availability and exploitation of raw materials in the lower Paleolithic of Lebanon / Corine Yazbeck -- Raw material use in west-central Jordan / Deborah I. Olszewski and U. Schurmans -- Lithic raw material availability and use at the epipaleolithic site of Tor al-Tareeq in west-central Jordan / Michael P. Neeley -- Prehistoric exploitation of Eocene flint in the al-Jafr Basin in southeastern Jordan / Philip Wilke, Leslie Quintero, and Gary A. Rollefson -- Lithic raw material procurement in the Acheulean of Gesher Benot Yaʹaqov, Israel / Christophe Delage -- Three periods, three patterns of chert exploitation in the Neolithic of Munhata (Central Jordan Valley, Israel) / Christophe Delage -- Prehistoric chert use in Cyprus / Carole McCartney -- Athkiakades ancient and modern: evidence of craftsmen and chert use from the Canadian Palaipaphos and Idalion Survey Projects in Cyprus / Sally Stewart